Incidence of Viral Agents in Children with CNS Affectation in the State of Zulia, Venezuela, during 2007 - John Bermúdez; Alegria Levy; Kelita González; Luz Espina; José Hernández; Leticia Porto; Nereida Valero (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
Introduction: Various viruses affect the central nervous system (CNS) causing encephalitis, mainly in pediatric patients. Objective: To determine the involvement of viral agents for central nervous system (CNS) infections in children in the State of Zulia, Venezuela during the year 2007. Patients and Methods: 109 samples of cerebrospinal fluid (CSF) and serum were collected from patients between 1 day and 14 years of age, who presented clinical symptoms suggestive of CNS involvement and whose conventional CSF bacteriological study proved negative. The CSF Albumin /serum relationship was determined in order to rule out contamination, resulting in 24 optimal pairs for determining the IgM and IgG antibodies specific for herpes simplex virus (HSV), Epstein Barr (EBV), Dengue fever, rubella, measles and Venezuelan Equine Encephalitis (VEE) using the ELISA technique. Results: Of the 24 cases examined, 15 (62.5%) were positive. The causative agents for encephalitis were 11 cases of Dengue (45.8%) (p<0.05), 3 VHS (12.5%) and 1 case of EBV (4.2%). There were no cases of rubella, measles or VEE. Pleocytosis with lymphocyte predominance was the most common finding in cases with confirmed viral encephalitis (VE), without significant differences related to the infecting viral agent. Conclusions: Results show that a significant proportion of encephalitis in children is due to viral agents, highlighting an increase in dengue cases with CNS affection in the region.